Adsorption of 1,10-Phenanthroline in HClO4 Solutions on Columnar-Structured Gold Electrodes : The Excluded Volume Effect - Gómez, M. M. (1996)
The electroadsorption of 1,10-phenanthroline on columnar Au electrodes from x M 1,10-phenanthroline + 0.1 M HClO4 aqueous solutions (5 × 10-4 ≤ x ≤ 5 × 10-3), at constant potential and 298 K, was studied using voltammetry, chronocoulometry, and ac impedance combined with scanning tunneling microscopy to characterize the substrate topography. The roughness factor (R) was defined as the ratio of the O-adatom monolayer electrodesorption charge at the columnar Au electrode to that at the initial smooth Au electrode. When both R and the molar 1,10-phenanthroline concentration (c) were kept constant, the degree of surface coverage by 1,10-phenanthroline (θ) diminished as R was increased. The θ vs c plots, irrespective of R, were interpreted by a Frumkin adsorption isotherm including a constant standard adsorption free energy. The analysis of parameters derived from adsorption isotherms reflects the existence of an excluded volume effect, as should be expected from the 1,10-phenanthroline molecule adsorption cross section, and the size of the smallest voids and crevices at the substrate determined by scanning tunneling microscopy.